Agreement concerning co-operation in suppressing illicit maritime and air trafficking in narcotic drugs and psychotropic substances in the Caribbean Area ([s.n.] [S.l.], 2003)
Seeks to ensure that suspect vessels and suspect aircraft are detected, identified, continuously monitored, and where evidence of involvement in illicit traffic is found, suspect vessels are detained for appropriate law enforcement action by responsible law enforcement authorities
Keywords: DRUG TRAFFIC